Superhydrophobic-superhydrophilic micropatterning: towards genome-on-a-chip cell microarrays - Geyer, Florian Ludwig; Ueda, Erica; Liebel, Urban; Grau, Nicole; Levkin, Pavel (Angewandte Chemie. International edition, 2011)
High-density cell microarrays based on superhydrophilic microspots separated by superhydrophobic barriers have been realized. The microspots absorb water solutions, while the barriers prevent cross-contamination, thus allowing the spots to be used as reservoirs for transfection mixtures and preventing cell proliferation and cell migration between the microspots. The picture shows four cell types after two days of culturing on the microarray.